Identity-formation and alterity in John Chrysostom's In epistulam ad Galatas commentarius - Chris L. de Wet (Acta Theologica)
The purpose of this study is to give account of the dynamics between Christian identity-formation and the problem of alterity in John Chrysostom’s In epistulam ad Galatas commentarius, one of the earliest extant commentaries on Paul’s Epistle to the Galatians. The study shows that Chrysostom envisions Christian identityformation as a subset of Paulinomorphism, to become like Christ one should also become like Paul. Chrysostom views Paulinomorphism as the operation of four interrelated discourses, namely the discourse of: a) transformation and mimesis; b) virtue and masculinisation; c) the zealotic, and; d) medicalisation. In order to examine how Paulinomorphism is applied to the problem of alterity, Chrysostom’s homilies In epistulam ad Galatas, especially the first homily in the series, are examined. Chrysostom opposes Judaizers, “Greeks”, Marcionites, Arians and Manichees in this commentary. The study therefore also represents an analysis of the Wirkungsgeschichte of Galatians.